Performance Enhancement of Solar PV Panels Using Splash Fill Cooling under Tropical Conditions - Risna, Daniar; Muhammad, Basyir; Arsy Febrina, Dewi; Aidi, Finawan; Yaman, .; Yassir, .; Muhammad, Ramzil (INTI International University, 2026)
This study examines the effectiveness of a splash fill cooling system in reducing the temperature of solar photovoltaic (PV) modules and enhancing their electrical performance under tropical conditions. Two identical 50 Wp PV modules were tested in parallel, with one equipped with the splash fill cooling system and the other serving as a reference without cooling. The cooling system was controlled by an Arduino Uno using threshold-based logic, which activated a water pump when the panel temperature exceeded 40°C. Real-time monitoring of temperature, voltage, and current was conducted over seven consecutive days (July 1–7, 2025). Results showed that splash fill cooling reduced panel temperature by an average of 4–5°C compared to the reference module. This reduction led to an increase in output current (2.7–3.3%) and power (2.7–4.3%), while voltage improvement remained modest at around 0.9%. Regression analysis revealed a strong negative correlation (R² > 0.85) between temperature and power output, confirming temperature as a dominant factor in PV efficiency. The findings highlight splash fill cooling as a simple, cost-effective, and water-efficient solution for improving PV performance in tropical climates, offering practical implications for small-scale and off-grid solar applications.